الفروق الضبطية بين الرسم المصحفى والرسم الإملائي - Ibnu Rawandhy N. Hula; Agussalim Beddu Mala (Al-Lisan: Jurnal Bahasa, 2021)
This study is related to the differences in diacritic marks used in writing the al-Quran (rasm mushaf) and conventional writing (rasm imla’i). This study aims to find aspects of the similarities and differences between the diacritic marks in two types of rasm, which are limited to five things. Namely: the sign of ya at the end of the word, the sign of sukun/silence, the position of the kasrah in tasydid, the position of the hamzah in a line of kasrah above the letter ya, and a long reading sign (madd). The type of research used is descriptive qualitative, with the literature and documentation method, which is carried out by reading books and various articles related to this research. The results showed the differences in diacritic marks between writing the al-Quran (rasm mushaf) and conventional writing (rasm imla’i). It consisted of several things, namely: 1) There is a similarity in writing between the rasm mushaf writing pattern and the conventional rasm pattern on letter differentiation, except for the writing of the letter ya at the end of the word, which is ignored in the writing of the mushaf (الهدى). 2) There are similarities in punctuation, especially in harakat, tasydid and hamzah, between the writing of the rasm mushaf and conventional writing, and this is unquestionably and acceptable. 3) There is a difference in the manuscripts printed in the eastern region, using the head of kha’ as a sign of sukun, ( ), whereas the ancient manuscripts use a circle like the one used by arithmetic people to denote the number zero ( ( ْ. 4) There are similarities in the writing of tasydid in the rasm mushaf and conventional rasm (imla’i), but the place for the kasrah mark with tasydid in the writing of the mushaf is under the letter (ــــّـــ), 5) Specifically for the hamzah sign that is in the middle and lined up in the kasrah, written ya on the rasm mushaf, by placing the head of the letter ‘ain with the vowel under ya' ( ) and this does not apply to the conventional rasm pattern/imla’ i الفَائِزُوْن) ). 6)The use of a long/madd sign (_ۤ_) above the madd letter, if there is a hamzah or a letter marked with sukun, it indicates an addition to the writing of the mushaf (القُرْءَانُ), meanwhile in use it is in a conventional rasm pattern (imla’i) such as which is in books, it shows hamzah mamdudah (القُرْآنُ)